PENDEKATAN DESAIN PONDASI JALAN DI JALUR PANTURA - Hedy Rahadian; Hendarto .; Julia Augustine (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2016)
Abstract Pantura Jawa Road, located in the corridor Java's north coast, is a national road which is very important in supporting economic growth in Indonesia, especially in Java economic growth. The road is located in the alluvial deposits in the category of soft soil that is "in the age of resen", meaning younger than 10,000 years in the geological period known as the Holocene. This condition causes a geotechnical failure in some road sections in the Pantura Road. Some conditions, such as overloading, rad hierarchy changes, and environmental conditions in the vicinity of the Pantura Road cause premature damage to pavement before the design life is reached. Pavement design basically assumes that geotechnical problems are solved with geotechnical approaches, including three performance factors that must be considered in the design of embankment on soft soil, namely freeboard, settlement, and the stability of the embankment. Directorate General of Highways has given design guides for road foundation on soft soil, which is in the Pavement Design Manual, which has a strong base approach with a design life of 40 years. Keywords: soft soil, damage to roads, road foundation, foundation design life  Abstrak Jalan Pantura yang terletak di koridor Pantai Utara Jawa merupakan jalan nasional yang sangat penting dalam mendukung pertumbuhan ekonomi Indonesia khususnya pertumbuhan ekonomi di Pulau Jawa. Jalan ini berada pada endapan alluvial dengan kategori tanah lunak yang "berumur resen", yaitu berumur kurang dari 10.000 tahun yang dalam periode geologi dikenal sebagai Holosen. Kondisi ini menyebabkan terjadinya kegagalan geoteknik di beberapa ruas di Pantura. Beberapa kondisi seperti overloading, peralihan hirarki jalan, dan kondisi lingkungan di sekitar Jalan Pantura menyebabkan kerusakan dini perkerasan sebelum umur rencananya tercapai. Desain perkerasan pada dasarnya mengasumsikan permasalahan geoteknik diselesaikan dengan pendekatan geoteknik, di antaranya tiga faktor kinerja yang harus diperhatikan dalam desain timbunan di atas tanah lunak adalah freeboard, penurunan, dan stabilitas timbunan. Direktorat Jenderal Bina Marga telah memberikan acuan perencanaan fondasi jalan di atas tanah lunak dalam Manual Desain Perkerasan yang memiliki prinsip strong base approach dengan umur rencana fondasi jalan 40 tahun. Kata-kata kunci: tanah lunak, kerusakan jalan, fondasi jalan, umur rencana fondasi